Active Control Of Building Structures By Using Active Mass Dampers With Linear Quadratic Regulator Control Law - Tri Maryono Rusadi; Yusuf Fuad; Siska Aprilia Hardiyanti (Universitas Negeri Surabaya, 2026)
This paper presents a theory of optimal control of building structures that are experienced in the earthquake load excitation by using an active mass damper. Control mechanism is done using active mass exerts a force on the control structure based on structural response is continuously measured. The concept of the Linear Quadratic Regulator (LQR) is used to calculate the required control force structure based on the input acceleration response that is measured using the accelerometer. optimal control system reliability was tested using shear building model is given Active Tuned Mass Damper (ATMD) five stories above the structure to provide the base acceleration excitation of disturbances in the form of a data record from the accelerogram. Test results for various load acceleration theory base, such as acceleration simulation of El-Centro N-S earthquake, Kobe earthquake, earthquake Pacoima, Northridge earthquake, Kern-County earthquake, and the Chichi earthquake showed optimal control is able to give good results. From the analysis and simulation results concluded that the optimal weighting matrix on the value of Q=1000 and the weighting matrix R=0.1 are able to reduce on the structural displacement of the top floor ranged from 19.80% - 58.90%, while for the reduction of the displacement velocity structure in the top floor between 18.24% - 54.18%.